Perancangan Man Hour Integrated Control Application pada Perusahaan Barbasis Project - Yuniarti, Rahayu Ary (Bina Nusantara University, 2013)
The purpose of the study is to analyze and design an integrated application for managing man hour called Manhour Integrated Control Application (MICA) for a project-based company. Users can easily monitor the progress of man hour’s usage using this application which can be accessed from different project sites. The methodology used in the study are (1) analysis towards the business process followed by identification of user requirement by interview with user, document analysis and literature study; and (2) design for database and user interface. The result expected from the study is web-based integrated application which can help user control and monitor project’s progress based on man hour and man power allocation and can be accessed from project site.